LAW ENFORCEMENT AGAINST CYBER CRIME IN ELECTRONIC TRANSACTIONS IN INDONESIA - TEGAR HARBRIYANA PUTRA; SUNNY UMMUL FIRDAUS (CV KULTURA DIGITAL MEDIA, 2024)
Law enforcement against cyber crime in electronic transactions in Indonesia is an increasingly crucial issue in the current digital era. The increasing use of information and communication technology has driven the growth of the digital economy, but has also given rise to various threats, including cyber crime. This article examines the law enforcement efforts carried out by the Indonesian government to overcome cyber crimes related to electronic transactions. This study analyzes existing regulations, including the Information and Electronic Transactions Law (UU ITE), as well as the role of law enforcement agencies in tackling cyber crime. Apart from that, this research also identifies challenges faced in the law enforcement process, such as limited resources, lack of coordination between agencies, and gaps in technological understanding among law enforcement officers. The research results show that although there has been significant progress in the legal and policy framework related to cyber crime, there are still many obstacles that reduce the effectiveness of law enforcement. Therefore, continuous efforts are needed to strengthen the capacity of law enforcement institutions, increase international cooperation, and update regulations so that they are in line with technological developments. Thus, it is hoped that law enforcement against cyber crime in electronic transactions in Indonesia can be more optimal in protecting the public and maintaining the integrity of the digital economy.